Stabilizing Layered Structure in Aqueous Electrolyte via O2‐Type Oxygen Stacking. Issue 27 (26th July 2022) - Xue, Liang; Wang, Chao; Liu, Hanghui; Li, Hao; Chen, Tingting; Shi, Zhengyi; Qiu, Ce; Sun, Mingqing; Huang, Yin; Huang, Jiangfeng; Sun, Jingwen; Xiong, Pan; et al.
Abstract: Despite the high energy density of O3‐type layered cathode materials, the short cycle life in aqueous electrolyte hinders their practical applications in aqueous lithium‐ion batteries (ALIBs). In this work, it is demonstrated that the structural stability of layered LiCoO2 in aqueous electrolyte can be remarkably improved by altering the oxygen stacking from O3 to O2. As compared to the O3‐type LiCoO2, the O2‐type LiCoO2 exhibits significantly improved cycle performance in neutral aqueous electrolyte. It is found that the structural degradation caused by electrophilic attack of proton can be effectively mitigated in O2‐type layered structure. With O2 stacking, CoO6 octahedra in LiCoO2 possess stronger CoO bonds while Co migration from Co layer to Li layer is strongly hampered, resulting in enhanced structural stability against proton attack and prolonged cycle life in aqueous electrolyte. The findings in this work reveal that regulating oxygen stacking sequence is an effective strategy to improve the structural stability of layered materials for ALIBs. Abstract : By altering the oxygen stacking sequence from O3 to O2, the layered structure stability can be significantly improved in the 1 m Li2 SO4 aqueous electrolyte. With stronger Co─O bonds, the O2‐LiCoO2 exhibits enhanced Co confinement in CoO6 octahedra. Meanwhile, the face‐sharing local environments of cations in O2‐LiCoO2 effectively suppress Co migration to Li layers, thus inhibiting the layered‐to‐spinel phase transition.